A clinical improvement of a idiopathic cervical dystonia in a patient treated with transdermal Rotigotine: a case-report - Mangiardi, Marilena; Alfano, Guido (Acta Biomedica Atenei Parmensis, 2020)
Dystonia is the third most common movement disorder. Cervical dystonia is the most common form of dystonia, a subtype of Primary Focal Dystonia due to the phasic and/or tonic involuntary contractions of different combinations of neck muscles, generally treated with good clinical results with botulin toxin type A or B injection. The etiology of cervical dystonia is still unknown. It was recently proposed that the cervical dystonia is due to malfunctioning of the head neural integrator, that result of impairment in cerebellar, basal ganglia, or proprioceptive feedback. The hypothesis of the existence of an electrical circuit that connects the basal ganglia with the cerebellum and the proprioception feedback, participating in the neural integrator of the head, explains that the damage at any point of the network can lead to motor deficits. Although dystonia is often associated with abnormal dopamine neurotransmission, dopaminergic drugs are not currently used to treat dystonia because there is a general view that they are ineffective. The results from the clinical trials and tests in mice suggest that the coactivation of D1 and D2 dopamine receptors may be an effective therapeutic strategy in some patients. These results support the assumption that dopamine receptors could be considered as targets for treating dystonia. Furthermore, a dopamine agonist-response dystonia in patients with an autosomal recessive L-amino acid decarboxylase deficiency, has been described in the scientific literature. We report a case of focal cervical dystonia successful treated with a dopamine agonist (D3>D2>D1) Rotigotine, a transdermal drug that induces a continuous dopaminergic stimulation.